Assessment of biomass and yield loss of maize caused by aerosols in heavily polluted agricultural areas of China based on APSIM model. (February 2020) - Zhao, Junfang; Kong, Xiangna; Xu, Hui; Zhang, Yanhong; Jiang, Yueqing
Abstract: In recent years, with the rapid economic growth, the government and the public pay more and more attention to the environmental effects caused by aerosols. In this study, the effects of aerosols on the biomass and yield of maize from 2001 to 2014 in heavily polluted agricultural areas of China were explored using global AErosol Robotic Network (AERONET) monitoring data, the Second Simulation of a Satellite Signal in the Solar Spectrum radiative transfer (6S) model, and the Agricultural Production Systems sIMulator (APSIM) crop growth model. Beijing, Xianghe, and Taihu stations were selected as research areas. The results showed that the APSIM-maize model was able to accurately simulate the interactions between maize and the climatic constraints in the maize planting areas at Beijing, Xianghe, and Taihu stations. Our results revealed that the aerosols reduced direct solar radiation, and that the decreasing trend was mainly due to the net radiation flux caused by aerosols. The average total radiation from 2001 to 2014 at Beijing, Xianghe, and Taihu stations decreased by 31.95%, 14.74%, and 28.30%, respectively, and the average maize biomass decreased by 34.12%, 20.78%, and 28.41%, respectively. As a result, the average maize yield at Beijing, Xianghe, and Taihu stations declined by 28.44%, 13.43%, and 14.89%, respectively. Our findings, particularly the understanding of the effect of aerosols on crop production, will have important implications for improving climate change impact studies and helping local agricultural production to cope with ongoing climate change. They could also benefit strategic decision-making related to future agricultural adaptation methods in China. Highlights: Global AERONET data, MODIS data, 6S radiative transfer model and APSIM crop model were applied. We evaluate the effects of aerosols on radiation in heavily polluted agricultural areas of China. We investigate the impacts of aerosols on the biomass and yield of maize in heavily polluted areas.